The Mediating Role of Firm Size in the Relationship Between DAR, ROA, and TATO on Firm Value - Lorina Siregar Sudjiman; Paul Eduard Sudjiman (JURNAL ILMIAH EDUNOMIKA, 2026)
From its foundation to its projected future performance, a company's stock price in the capital market reflects public perception and trust in the company's performance, which together make up the company's value. This study seeks to examine the relationship between company value, debt-to-asset ratios (DAR), return on assets (ROA), and total asset turnover (TATO), controlling for company size. Multiple linear regression analysis is the tool used in this study's quantitative methodology. Of the businesses listed on the Indonesia Stock Exchange between 2021 and 2024, 21 were from the food and beverage subsector. This study made use of secondary data that was analysed with the help of IBM SPSS. Debt to Asset Ratio (DAR) does not impact company value, according to the data. In contrast, TATO and Return on Assets (ROA) significantly impact the value of a company. There is no moderating effect of firm size on the correlation between DAR and TATO on a company's value. On the flip side, the correlation between ROA and a company's worth might be dampened by its size. Keywords: Firm value, debt to asset ratio, return on assets, total asset turnover, and firm size